الإجراءات الجزائية في قضايا العنف الأسري: دراسة في ضوء قانون مناهضة العنف الأسري في إقليم كوردستان-العراق رقم 8 لسنة 2011 - أ.م.د. مسعود حميد إسماعيل (QALAAI ZANIST SCIENTIFIC JOURNAL, 2017)
Domestic violence is a social phenomenon experienced by many societies; this phenomenon is the product of what gripped function Social Latency in the family system changes originated negative phenomena of modern civilization. Domestic violence and poses a major threat to the life of the individual and society, it is from the point of striking the first cell of society imbalance, which hampered the performance of social, educational and basic functions, on the other hand it helps to reproduce patterns of behavior and relationships abnormal among family members, which requires attention to scientific this phenomenon to reduce them and prevention, which may result from the consequences. Because of the widespread manifestations of domestic violence and its negative effects on individuals, family and public order, and on the evolution of society and its development, and in order to protect the family and to take legal action for the safety and stability and the prevention of domestic violence preventive means before it happens and discuss reform and therapeutic solutions after the fact, the legislator Kurdistan finds it necessary legislation Victims of Domestic Violence Act in Kurdistan-Iraq region No. (8) for the year (2011(.